Whole-Genome Sequence of Weissella ceti Strain WS08, Isolated from Diseased Rainbow Trout in Brazil - Figueiredo, H. C. P. (American Society for Microbiology, 2014)
We report here the complete genome sequence of Weissella ceti strain WS08, an emerging pathogen to farm-raised rainbow trout. The genome of strain WS08 is composed of a circular chromosome with 1,355,853 bp and a G+C content of 40.78%.